solve and simplify the equation

Algebra
Tutor: None Selected Time limit: 1 Day

(3u-1)(6-u)=0

Jun 27th, 2015

Thank you for the opportunity to help you with your question!

(3u-1)(6-u)=0

18u+3u^2-6-u=0

3u^2-6+17u=0

by using quadratic formula

u= 1/3   , u = -6


Please let me know if you need any clarification. I'm always happy to answer your questions.
Jun 27th, 2015

hi its saying that one of my answers is incorrect 

Jun 27th, 2015

u= 0.37   , u = -6


try this .................then tell me :)

Jun 27th, 2015

u= 1/3   , u = 6 this is correct answer
sorry for the typing mistake earlier

Jun 27th, 2015

ok so u=1/3 or -6 was right but u must = something else

Jun 27th, 2015

dear this is the correct answer........

u= 1/3   , u = 6 this is correct answer
sorry for the typing mistake earlier

Jun 27th, 2015

Did you know? You can earn $20 for every friend you invite to Studypool!
Click here to
Refer a Friend
...
Jun 27th, 2015
...
Jun 27th, 2015
Dec 4th, 2016
check_circle
Mark as Final Answer
check_circle
Unmark as Final Answer
check_circle
Final Answer

Secure Information

Content will be erased after question is completed.

check_circle
Final Answer